Letteratura postmoderna e comunicazione pubblicitaria, problemi teorici e analisi testuali - Bio, Mariangela <1975> (Alma Mater Studiorum - Università di Bologna, 2009)
Premise: In the literary works of our anthropological and cultural imagination, the various languages and the different discursive practices are not necessarily quoted, expressly alluded to or declared through clear expressive mechanisms; instead, they rather constitute a substratum, a background, now consolidated, which with irony and intertextuality shines through the thematic and formal elements of each text. The various contaminations, hybridizations and promptings that we find in the expressive forms, the rhetorical procedures and the linguistic and thematic choices of post-modern literary texts are shaped as fluid and familiar categories. Exchanges and passages are no longer only allowed but also inevitable; the post-modern imagination is made up of an agglomeration of discourses that are no longer really separable, built up from texts that blend and quote one another, composing, each with its own specificities, the great family of the cultural products of our social scenario. A literary work, therefore, is not only a whole phenomenon, delimited hic et nunc by a beginning and an ending, but is a fragment of that complex, dense and boundless network that is given by the continual interrelations between human forms of communication and symbolization. The research hypothesis: A vision is delineated of comparative literature as a discipline attentive to the social contexts in which texts take shape and move and to the media-type consistency that literary phenomena inevitably take on. Hence literature is seen as an open systematicity that chooses to be contaminated by other languages and other discursive practices of an imagination that is more than ever polymorphic and irregular. Inside this interpretative framework the aim is to focus the analysis on the relationship that postmodern literature establishes with advertising discourse. On one side post-modern literature is inserted in the world of communication, loudly asserting the blending and reciprocal contamination of literary modes with media ones, absorbing their languages and signification practices, translating them now into thematic nuclei, motifs and sub-motifs and now into formal expedients and new narrative choices; on the other side advertising is chosen as a signification practice of the media universe, which since the 1960s has actively contributed to shaping the dynamics of our socio-cultural scenarios, in terms which are just as important as those of other discursive practices. Advertising has always been a form of communication and symbolization that draws on the collective imagination – myths, actors and values – turning them into specific narrative programs for its own texts. Hence the aim is to interpret and analyze this relationship both from a strictly thematic perspective – and therefore trying to understand what literature speaks about when it speaks about advertising, and seeking advertising quotations in post-modern fiction – and from a formal perspective, with a search for parallels and discordances between the rhetorical procedures, the languages and the verifiable stylistic choices in the texts of the two different signification practices. The analysis method chosen, for the purpose of constructive multiplication of the perspectives, aims to approach the analytical processes of semiotics, applying, when possible, the instruments of the latter, in order to highlight the thematic and formal relationships between literature and advertising. The corpus: The corpus of the literary texts is made up of various novels and, although attention is focused on the post-modern period, there will also be ineludible quotations from essential authors that with their works prompted various reflections: H. De Balzac, Zola, Fitzgerald, Joyce, Calvino, etc… However, the analysis focuses the corpus on three authors: Don DeLillo, Martin Amis and Aldo Nove, and in particular the followings novels: “Americana” (1971) and “Underworld” (1999) by Don DeLillo, “Money” (1984) by Martin Amis and “Woobinda and other stories without a happy ending” (1996) and “Superwoobinda” (1998) by Aldo Nove. The corpus selection is restricted to these novels for two fundamental reasons: 1. assuming parameters of spatio-temporal evaluation, the texts are representative of different socio-cultural contexts and collective imaginations (from the masterly glimpses of American life by DeLillo, to the examples of contemporary Italian life by Nove, down to the English imagination of Amis) and of different historical moments (the 1970s of DeLillo’s Americana, the 1980s of Amis, down to the 1990s of Nove, decades often used as criteria of division of postmodernism into phases); 2. adopting a perspective of strictly thematic analysis, as mentioned in the research hypothesis, the variations and the constants in the novels (thematic nuclei, topoi, images and narrative developments) frequently speak of advertising and inside the narrative plot they affirm various expressions and realizations of it: value ones, thematic ones, textual ones, urban ones, etc… In these novels the themes and the processes of signification of advertising discourse pervade time, space and the relationships that the narrator character builds around him. We are looking at “particle-characters” whose endless facets attest the influence and contamination of advertising in a large part of the narrative developments of the plot: on everyday life, on the processes of acquisition and encoding of the reality, on ideological and cultural baggage, on the relationships and interchanges with the other characters, etc… Often the characters are victims of the implacable consequentiality of the advertising mechanism, since the latter gets the upper hand over the usual processes of communication, which are overwhelmed by it, wittingly or unwittingly (for example: disturbing openings in which the protagonist kills his or her parents on the basis of a spot, former advertisers that live life codifying it through the commercial mechanisms of products, sons and daughters of advertisers that as children instead of playing outside for whole nights saw tapes of spots.) Hence the analysis arises from the text and aims to show how much the developments and the narrative plots of the novels encode, elaborate and recount the myths, the values and the narrative programs of advertising discourse, transforming them into novel components in their own right. And also starting from the text a socio-cultural reference context is delineated, a collective imagination that is different, now geographically, now historically, and from comparison between them the aim is to deduce the constants, the similarities and the variations in the relationship between literature and advertising.